Network analysis and intra-team activity in attacking phases of professional football - Gama, J.; Passos, P.; Davids, K.; Relvas, H.; Ribeiro, J.; Vaz, V.; Dias, G. (International Journal of Performance Analysis in Sport, 2014)
In this study we sought to verify whether network analyses could be used to identify key players in attacking phases of a professional football match and establish the main interactions and preferential linkages between attacking teammates during competitive performance. For this purpose, we examined circulation of the ball on field during randomly selected attacking phases of play in a video-taped Portuguese Premier League match. We observed six matches and notated 1488 collective attacking actions, including: passes completed, passes received, and crosses involving a total of 4126 intra-team interactions (eg., 2063 passes and crosses performed and 2063 passes and crosses received). We used Amisco® software to perform quantitative and qualitative analyses of the attacking actions. Results indicated how key individual players are instrumental in orchestrating team performance, exerting a powerful influence in creating attacking patterns of play. Our findings may help coaches and sports scientists quantify the contributions and interactions of individual team members through analysis of their relevant actions in team sports like football.